Family firm research: A review - Qiang Cheng (China Journal of Accounting Research, 2014)
This article reviews family firm studies in the finance and accounting literature, primarily those conducted using data from the United States and China. Family owners have unique features such as concentrated ownership, long investment horizon, and reputation concerns. Given the distinguishing features of family ownership and control, family firms face unique agency conflicts. We discuss the agency problems in family firms and review the findings of recent family firm studies. We call for more research to understand the unique family effects and encourage more research on Chinese family firms.Part I of the article discusses the fundaments of family firms: the prevalence of and the agency conflicts within family firms. Part II summarizes the findings of recent U.S. family firm studies. It reviews the evidence on the family firm premium (how, which, and when family firms are associated with a valuation premium), the manifestation of the agency conflict between majority and minority shareholders in family firms, earnings quality and corporate disclosure, and the determinants of family ownership and control. Part III discusses the prevalence and characteristics of Chinese family firms and reviews the findings of related studies. The article concludes with some suggestions for future research.
Keywords: G30; G32; G38; M20; M41; 650; Family firms; Ownership structure; Agency problems; Controlling owners; Minority owners